2014
DOI: 10.1007/s12017-014-8321-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Phosphorylation Transcriptome Alterations in Human Amyotrophic Lateral Sclerosis Spinal Cord and Blood

Abstract: Origins of onset and progression of motor neurodegeneration in amyotrophic lateral sclerosis (ALS) are not clearly known, but may include impairment of mitochondrial bioenergetics. We used quantitative PCR approaches to analyze the mitochondrial oxidative phosphorylation (OXPHOS) transcriptomes of spinal cord tissue and peripheral blood mononuclear cells (PBMC) from persons with sporadic ALS compared with those without neurological disease. Expression measurements of 88 different nuclear (n) and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…Our studies of human cervical spinal cord and peripheral blood MNCs from sALS subjects found reduced mtDNA gene expression and impaired mitobiogenesis signaling [29]. We do not yet know the origin(s) of this deficit in mitobiogenesis in ALS, except that it does not appear to be derived primarily from the decreased mtDNA gene expression [30].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our studies of human cervical spinal cord and peripheral blood MNCs from sALS subjects found reduced mtDNA gene expression and impaired mitobiogenesis signaling [29]. We do not yet know the origin(s) of this deficit in mitobiogenesis in ALS, except that it does not appear to be derived primarily from the decreased mtDNA gene expression [30].…”
Section: Discussionmentioning
confidence: 82%
“…By studying cells from living patients with associated clinical data, we hope to learn more about sporadic disease. Toward this goal, a recent study from our laboratory showed decreased mitochondrial-encoded gene expression in peripheral blood mononuclear cells (MNCs) of ALS patients compared with control, suggesting a systemic bioenergetic impairment [29]. If motor neurons differentiated from ALS iPSCs display the same mitochondrial dysfunction seen in postmortem tissue, they may be used as a model of sALS.…”
mentioning
confidence: 99%
“…Hirano et al reported a 65-year-old ALS patient whose muscle biopsy showed 10% ragged- and alterations of the mitochondrial genome and transcriptome. [8][9][10][11][12][13][14] There are also indications that mtDNA deletions are more common in individuals with sporadic ALS as compared to healthy controls. 15 Mitochondrial dysfunction in ALS is often regarded as secondary following the exposure of mtDNA to increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods for acquisition of cervical spinal cord, isolation by LCM of motor neurons from cervical spinal cord sections, RNA isolation and amplification, cDNA generation and qPCR of mitochondrial genes have been previously described [26,38]. Methods for generation and quantitation of multiplex RNA-seq libraries from these amplified RNA's have also been described [38].…”
Section: Methodsmentioning
confidence: 99%